Project managers competency on project performance of green toll road development project in Indonesia - Mairizal Mairizal; Rahmat Alifiardi; Gilang Ardi Pratama; Mohd Zaimi Abd Majid; Shek Poi Ngian (Universitas Mercu Buana, 2023)
The Green Road Construction development program is a program that has the potential to reduce carbon emissions from road construction. Currently, the Government of the Republic of Indonesia through the Ministry of Public Works and Public Housing together with the Toll Road Business Entity continues to strive to provide the best service to the community using Toll Roads that are applied to all Toll Roads in Indonesia, especially Green Toll Roads. At the implementation stage, it has not been able to run smoothly because there are several constraining factors such as social and environmental aspects. For this reason, this study aims to find out what factors are needed by a Project Manager who carries out the construction. References are taken from various journals and articles that discuss green toll roads around the world and in Indonesia. This research is a combination of qualitative and quantitative (mixed methods) by distributing questionnaires to several respondents. The results of the factor analysis show that the Project Performance factor (Y) is strongly influenced by the determinant factors namely Knowledge (X1) in terms of Time (X1.3), Cost (X1.4) and Procurement (X1.7). Henceforth, project performance (Y) is also influenced by Knowledge (X1), Skill (X2), and Tools & Techniques (X3). Meanwhile, on the other hand, the Project Performance factor (Y) is also influenced by the Green Toll Road (Z).